2012
DOI: 10.1007/s00403-012-1303-8
|View full text |Cite
|
Sign up to set email alerts
|

The expression of serotonin transporter protein correlates with the severity of psoriasis and chronic stress

Abstract: Psoriasis may be worsened by stress and mood disorders. There is an increased expression of the serotonin transporter protein (SERT) in involved psoriatic skin as compared to non-involved psoriatic skin and normal skin. The aim of this study was to investigate if the increased expression of SERT in psoriasis correlates with the severity of disease, chronic stress, and depression. Biopsies from involved and non-involved skin from the back of 20 patients with chronic plaque psoriasis were immunohistochemically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…This observation was also accompanied by accumulation of sphinganine, palmitoyl sphingomyelin, and stearoyl sphingomyelin, with a sphingosine 1-phosphate decrease in the psoriasis group. In addition, the 3.9-fold increase in serotonin level may be of particular interest because expression of its transporter protein, SERT, is altered in psoriatic lesions, which may contribute to inflammatory processes in the skin (Thorslund et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This observation was also accompanied by accumulation of sphinganine, palmitoyl sphingomyelin, and stearoyl sphingomyelin, with a sphingosine 1-phosphate decrease in the psoriasis group. In addition, the 3.9-fold increase in serotonin level may be of particular interest because expression of its transporter protein, SERT, is altered in psoriatic lesions, which may contribute to inflammatory processes in the skin (Thorslund et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Most of these reports have studied oral lichen planus, and the results are controversial [16][17][18][19][20][21][22][23][24][25] . Some recent immunohistochemical studies have shown that compared to normal skin, the expression of serotonin and its receptors in epithelial and adnexal structures was increased in the lesions of those with chronic inflammatory skin disease, including psoriasis, chronic eczema, allergic contact dermatitis, and atopic dermatitis 14,15,[26][27][28][29][30] . To our knowledge, our current study is the first to investigate serotonin expression in the lesions of LP.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, psoriatic patients achieving Ն75% improvement from baseline PASI score have a greater reduction in Zung Depression Scale score compared with patients achieving Ͻ75% improvement from baseline PASI score. A recent study conducted by Thorslund et al 75 showed a positive correlation (r ϭ 0.53; P Ͻ .05) between PASI and the numbers of serotonin transporter protein-positive dendritic cells in the epidermis of involved psoriatic skin. As such, it was suggested that the serotonergic system in the skin may be involved in the chronic inflammation of psoriatic skin.…”
Section: Potential Benefits Of Tnf-␣ Antagonists On Depressionmentioning
confidence: 89%